2015
DOI: 10.4238/2015.july.28.7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of wild Prunus cerasifera Ehrhart (wild cherry plum) in China revealed by simple-sequence repeat markers

Y Li2,
et al.

Abstract: ABSTRACT. Simple-sequence repeat (SSR) markers were employed to assess the genetic diversity of wild Prunus cerasifera Ehrhart (wild cherry plum) in China. Fourteen SSR primer pairs generated a total of 94 alleles (90 were polymorphic, accounting for 95.74%), with a mean of 6.71 alleles per locus. The number of alleles detected at each locus ranged from 2 at BPPCT 028 to 13 at BPPCT 002, with an average of 6.71 alleles per locus. Nei's genetic diversity ranged from 0.0938 to 0.4951 and Shannon's information in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Thus, our data suggest that Turkish P. cerasifera germplasm has a high genetic diversity that is similar to that seen in nearby countries. In general, other studies have indicated that P. cerasifera germplasm population structure is simple with two to three subpopulations (Ayanoğlu et al, 2007;Zhao et al, 2015;Urbanovich et al, 2017). In our work, the dendrogram analysis revealed two main clusters with a small third group of five accessions.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Thus, our data suggest that Turkish P. cerasifera germplasm has a high genetic diversity that is similar to that seen in nearby countries. In general, other studies have indicated that P. cerasifera germplasm population structure is simple with two to three subpopulations (Ayanoğlu et al, 2007;Zhao et al, 2015;Urbanovich et al, 2017). In our work, the dendrogram analysis revealed two main clusters with a small third group of five accessions.…”
Section: Discussionsupporting
confidence: 60%
“…According to this range, our mean genetic diversity value was 0.78. Ayanoglu et al (2007) and Zhao et al (2015) found the lowest levels of genetic dissimilarity in their studies which examined Turkish (0.09) (this extremely low value may be the result of the small number of accessions studied) and Chinese (0.33) germplasm. Other research using P. cerasifera accessions from France, Iran and Belarus had mean diversity values of 0.65, 0.68 and 0.72, respectively (Horvath et al, 2008;Wöhrmann et al, 2011;Urbanovich et al, 2017), which agree with the level of diversity seen in our Turkish material.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations